INTERAKSI AL-QUR’AN DAN PERILAKU TERPUJI MAHASISWA DALAM AKTIVITAS PERKULIAHAN PADA FAKULTAS TARBIYAH DAN KEGURUAN UIN AR-RANIRY BANDA ACEH (The Interaction of The Qur'an and Students' Praise Behavior in Lecture Activities at The Tarbiyah Faculty and Teaching at Ar-Raniry State Islamic University of Banda Aceh) - Mumtazul Fikri (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2022)
This study aims to see the effect of the interaction of the Qur'an on the formation of commendable behavior in students of the Tarbiyah and Teacher Training Faculty of Universitas Islam Negeri Ar-Raniry. This research is a correlation research, which is a study conducted to determine the level of relationship between two or more variables. This research uses quantitative analysis method using Product-Moment correlation measurement technique. The results showed that for the quality of the interaction of the Qur'an 29.59% students of the Tarbiyah and Teacher Training Faculty of UIN Ar-Raniry very often interacted with the Qur'an, 67.35% of them often and 3.06% moderate. So it can be concluded that the quality of the interaction of the Qur'an by the students of the Tarbiyah Faculty and Teacher Training at UIN Ar-Raniry is good. For the quality of commendable behavior, it shows that 22.4% of the students of the Tarbiyah and Teacher Training Faculty of UIN Ar-Raniry behave with Very Praiseworthy behavior, 74.5% of them behave Commendable and 3.06% behave Moderately. So it can be concluded that the quality of commendable behavior of the students of the Tarbiyah and Teacher Training Faculty of UIN Ar-Raniry is good. The correlation between the interaction of the Qur'an and commendable behavior is obtained by rxy = + 0.67, while the r product moment table with N = 100 (which is closest to the number 98) shows a critical price of r 95% = 0.195. The value of rxy = + 0.67 is far beyond the critical value, so it can be concluded that the value of r is significant at the 95% confidence level and Ho is rejected. The conclusion is that the intensity of the interaction of the Qur'an has a significant influence on the formation of commendable behavior for the students of the Faculty of Tarbiyah and Teacher Training at UIN Ar-Raniry.